Measuring the desire of the Employees of the Ministry of Hajj and Umrah in Saudi Arabia to implement Kaizen - Siddiq, Nesreen AbdulRaheem; Al-Kubaisy, Zenah Mahmoud Majeed (Journal of Economic, Administrative and Legal Sciences, 2024)
The Ministry of Hajj and Umrah in Saudi Arabia endeavors to achieve one of the Kingdom’s Vision 2030 goals, which is to have 30 million pilgrims perform Umrah by 2030. To achieve the highest levels of quality services for this huge number of pilgrims, it is necessary to adopt management models that improve performance and enhance operations. The continuous improvement model “Kaizen” is one of the tools to improve the services for pilgrims. This study aims to measure the desire of the employees of the Ministry of Hajj and Umrah to implement Kaizen. The inductive quantitative method was adopted, and the data was collected using the questionnaire tool. The study sample consisted of 333 employees from the ministry. The questionnaire included questions related to the components of Kaizen (Plan, Do, Check, Act), as these components represent the independent variables against the dependent variable, which is the desire of the ministry’s employees to implement Kaizen. The data was analyzed through the SPSS. The validity and reliability of the study tool was verified through an experimental sample of 30 employees from the ministry. The results indicated that there is a statistically significant impact at (∝<0.05) of the components of Kaizen on the employees’ desire to implement Kaizen. The study recommends that in order to achieve success with Kaizen, the senior management should make continuous creative efforts through on-job competency programs on the methods and skills of implementing Kaizen, with a focus on sizing operations to eliminate waste. *Acknowledgments: This project was funded by the Institutional Funding Program under Grant No. (IFPAS: 70-245-1443). Therefore, the researchers are grateful for the technical and financial support provided by the Research and Innovation Agency of the Ministry of Education and King Abdulaziz University in Jeddah, Kingdom of Saudi Arabia.